A Longitudinal Study of Traumatic Play Activity Using the Children's Developmental Play Instrument (CDPI). (2nd January 2016) - Chazan, Saralea; Kuchirko, Yana; Beebe, Beatrice; Sossin, K. Mark
ABSTRACT: This is a longitudinal study of traumatic play activity using The Children's Developmental Play Instrument (CDPI). The CDPI is a multidimensional observational measure based upon a four-level model of play activity: Segmentation; Descriptive Analysis; Component Analysis and Functional Analysis. We studied one child and his mother, participants in a post-9/11 supportive intervention project. In this research children were filmed playing for 10 minutes with their mother and then10 minutes with a trained clinician. Mother and child were followed for a period of eight years by viewing annual videotaped play sessions. Findings revealed the CDPI was an effective tool in assessing the evolution of traumatic play and fantasy play over time using both qualitative and quantitative analyses. Of particular interest were the effects of trauma as evidenced in coping-defensive strategies observed in the play activity as play styles.